Answer:
B. ![\frac{67}{10} x + 9](https://tex.z-dn.net/?f=%5Cfrac%7B67%7D%7B10%7D%20x%20%2B%209)
Step-by-step explanation:
Simplify the expression. Remember to go by the order of operations, or PEMDAS.
1) First, distribute the numbers outside of the set of parentheses to the terms inside the set of parentheses next to them. Then, simplify the fractions.
![3(\frac{7}{5} x + 4) -2 (\frac{3}{2} -\frac{5}{4} x)](https://tex.z-dn.net/?f=3%28%5Cfrac%7B7%7D%7B5%7D%20x%20%2B%204%29%20-2%20%28%5Cfrac%7B3%7D%7B2%7D%20-%5Cfrac%7B5%7D%7B4%7D%20x%29)
![\frac{21}{5}x + 12 - \frac{6}{2} + \frac{10}{4} x](https://tex.z-dn.net/?f=%5Cfrac%7B21%7D%7B5%7Dx%20%2B%2012%20%20-%20%5Cfrac%7B6%7D%7B2%7D%20%2B%20%5Cfrac%7B10%7D%7B4%7D%20x)
![\frac{21}{5} x + 12 - 3 + \frac{10}{4} x](https://tex.z-dn.net/?f=%5Cfrac%7B21%7D%7B5%7D%20x%20%2B%2012%20-%203%20%2B%20%5Cfrac%7B10%7D%7B4%7D%20x)
2) Finally, combine like terms. (This means to add or subtract constants and to add or subtract terms with the same variables.) You may need to convert terms to the same denominator in order to do so easier. Then, reduce the fraction.
![\frac{21}{5} x + 9 + \frac{10}{4}x \\\frac{84}{20}x + \frac{50}{20}x + 9 \\\frac{134}{20}x + 9 \\\frac{67}{10}x + 9](https://tex.z-dn.net/?f=%5Cfrac%7B21%7D%7B5%7D%20x%20%2B%209%20%2B%20%5Cfrac%7B10%7D%7B4%7Dx%20%5C%5C%5Cfrac%7B84%7D%7B20%7Dx%20%2B%20%5Cfrac%7B50%7D%7B20%7Dx%20%2B%209%20%5C%5C%5Cfrac%7B134%7D%7B20%7Dx%20%2B%209%20%5C%5C%5Cfrac%7B67%7D%7B10%7Dx%20%2B%209)
Thus, the answer is
.
Answer:
FBC
Step-by-step explanation:
It's the only one at the front of the box
Answer:
Step-by-step explanation:Given that the numerator of a given fraction is 4 less than its denominator.
Also given that 3 is subtracted from the numerator and 5 is added to the denominator, the fraction becomes one by fourth .
Let the fraction be
Since the numerator of a given fraction is 4 less than its denominator we have,
Numerator=Denominator-4
⇒ a=b-4
Since 3 is subtracted from the numerator and 5 is added to the denominator, the fraction becomes one by fourth we have
4(a-3)=1(b+5)
4a-12=b+5
4a-b=17
4(b-4)-b=17 ( ∵ a=b-4)
4b-16-b=17
3b=17+16
3b=33
⇒ b=11
Now put b=11 in a=b-4 we get
a=11-4
⇒ the fraction is a/b=7/11